2003
DOI: 10.1007/s10072-003-0136-9
|View full text |Cite
|
Sign up to set email alerts
|

Distal-proximal differences in limb apraxia in corticobasal degeneration but not progressive supranuclear palsy

Abstract: Limb apraxia is an important diagnostic sign of cortico-basal degeneration (CBD), although it is also found in progressive supranuclear palsy (PSP). We investigated whether the severity of apraxia differed between proximal and distal arm movements in the two diseases, as suggested by their differing patterns of motor impairment. We studied 24 CBD patients, 25 PSP patients, and 19 healthy controls using a battery of cognitive tests and an ideomotor apraxia test that examined imitation of hand and of whole arm g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
4
5
0
Order By: Relevance
“…These impairments were present in both self-induced gestures and imitation. Other authors have also reported deficits in finger movements (Okuda et al 1992;Soliveri et al 2003;Graham et al 1999;Pillon et al 1995, Fitzgerald et al 2007). More recently, Leiguarda and colleagues (2003) examined the performance of patients on ten finger postures and movements and showed that all his patients presented with limb-kinetic apraxic deficits.…”
Section: Limb-kinetic Apraxia In Cbsmentioning
confidence: 90%
See 1 more Smart Citation
“…These impairments were present in both self-induced gestures and imitation. Other authors have also reported deficits in finger movements (Okuda et al 1992;Soliveri et al 2003;Graham et al 1999;Pillon et al 1995, Fitzgerald et al 2007). More recently, Leiguarda and colleagues (2003) examined the performance of patients on ten finger postures and movements and showed that all his patients presented with limb-kinetic apraxic deficits.…”
Section: Limb-kinetic Apraxia In Cbsmentioning
confidence: 90%
“…Unfortunately, as is the case with many studies in stroke patients, most studies examining apraxia in CBS patients have failed to include such tasks (See Table 3 for a summary) (Pharr et al 2001;Spatt et al 2002;Leiguarda et al 2003;Soliveri et al 2003), and therefore it is not possible to determine whether the impairment is due to conceptual or production deficits. The studies that have included gesture identification and recognition tasks, however, have shown quite consistently that most patients with CBS do not have impairment in their conceptual knowledge of actions (Leiguarda et al 1994;Jacobs et al 1999;Salter et al 2004;Soliveri et al 2005).…”
Section: The Conceptual Praxis System and Cbsmentioning
confidence: 96%
“…Moreover, the authors correlated the scores of the imitation test with the scores of the demonstration‐of‐use of objects test‐one of the traditional detection measures of apraxia‐and found that the two tests measured approximately the same abilities ( r = 0.80). Since then, the test is widely used in studies assessing limb IMA (20–23) and is considered to evaluate well ‘distal vs proximal movements’ (23).…”
Section: Discussionmentioning
confidence: 99%
“…Apraxia has also been identified in movement disorders where the basal ganglia are involved such as Parkinson's disease, CBS and PSP. 9 17 55 56 57 Even in the early stages of Parkinson's disease, difficulty with praxis has been identified, which appear to correlate with an activation shift from left parietal to left frontal areas shown on fMRI. 58 The limb-kinetic apraxia found in patients with Parkinson's disease appears to be largely independent from bradykinesia or other symptoms, once again indicating that the problem appears to be one concerning dexterity.…”
Section: The Neurophysiology Of Apraxiamentioning
confidence: 99%